Descriptive characterization of measles in Kebbi State, Nigeria, 2013-2017 - Hashim Abdulmumin Bala; Mohammed Yahaya; Nyampa Barau; Lukman Surajudeen; Ismail Raji Abdullateef; Charles Rahab Amaza (Journal of Interventional Epidemiology and Public Health)
Introduction: Measles is a highly infectious, viral disease, and endemic in developing countries. In Nigeria, and other countries in sub-Saharan Africa (SSA), the peak of transmission is from October to March. The disease is still common and very often, fatal in developing countries. This analysis was conducted to describe the characteristics of suspected measles cases in Kebbi State between 2013 and 2017, describe the outcome status and case fatality rates, and identify factors associated with outcome status.